More on the penetration of rigid projectiles in metallic targets. (December 2020) - Rosenberg, Z.; Vayig, Y.; Kositski, R.; Malka-Markovitz, A.
Highlights: The deceleration of a rigid projectile penetrating a metallic target is explored by numerical simulations in order to highlight the role of the target's inertia during penetration. We propose a simplified model for the penetration depths of rigid projectiles impacting metallic target- entrance phase. We derive a new relation for the resisting stresses (Rt) exerted by metallic targets on rigid projectiles. Abstract: The deceleration of a rigid projectile penetrating a metallic target is explored through numerical simulations with very different targets, in order to highlight the role of the target's inertia during penetration. These simulations also highlight the cavitation phenomenon through which, above a certain threshold velocity, the target's inertia is playing an important role in the penetration process. In addition, we propose a simplified model for the entrance phase effect on the penetration depths of rigid projectiles impacting metallic targets. We also explore the role of Poisson's ratio in determining the resistance to penetration of a metallic target, and derive a new relation for the resisting stresses exerted by these targets on ogive-nosed rigid projectiles.